Optimalization Of Water Cooled Chiller Through Real-Time Data Analysis - Muhammad Hanif Ulwani; Fahrudin Ulwani; Fitri Wahyuni (International Journal of Marine Engineering Innovation and Research, 2024)
Building heating, ventilation, and air conditioning (HVAC) systems are among the most critical facilities with the most significant energy consumption. This article is based on the issues faced by PT X regarding the importance of visual analytics in energy audits and the performance evaluation of water-cooled chillers and cooling towers. The research methodology used is descriptive qualitative with a quantitative approach, where primary data is obtained based on observations of the machines owned by PT X. The approach taken involves the application of spreadsheets as a system for processing operational data and Looker Studio for real-time data visualization, aimed at understanding performance and energy consumption. The research results show that visualization with the Looker Studio platform provides a solution for PT X to improve the efficiency and effectiveness of the company's performance. In addition, the analysis conducted over six months on the coefficient of performance of a 2,000 TR water-cooled chiller showed a highest value of 21.5 and a lowest value of 13.31, while the highest efficiency of the cooling tower reached 98% and the lowest was 74%.